1995
DOI: 10.1164/ajrccm.152.3.7663777
|View full text |Cite
|
Sign up to set email alerts
|

Arousal responses from apneic events during non-rapid-eye-movement sleep.

Abstract: Patients with obstructive sleep apnea (OSA) experience severe sleep disruption and consequent daytime sleepiness. Current arousal scoring criteria show that some obstructive apneic events do not end in a recognizable cortical electroencephalographic (EEG) arousal. It is not known whether events that end in an obvious EEG arousal differ from those that do not, in terms of EEG frequency changes during the apneic event, the respiratory effort developed prior to apnea termination, the degree of the postapneic incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

8
84
1
3

Year Published

1998
1998
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 129 publications
(97 citation statements)
references
References 22 publications
8
84
1
3
Order By: Relevance
“…Moreover, the majority of MAS activations occurred more frequently after respiratory events with arousal response than those without, as previous studies have also reported for the MAS and other craniofacial muscles. [2][3][4]23 Although previous studies have shown that cardiac arousals without visually detectable EEG changes have been detected after respiratory events, 18,21,23,28 these respiratory events were found to be rarely associated with MAS contractions. This is consistent with the findings of the recent studies in which respiratory efforts and electromyography of the tongue muscles were assessed in relation to respiratory events.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the majority of MAS activations occurred more frequently after respiratory events with arousal response than those without, as previous studies have also reported for the MAS and other craniofacial muscles. [2][3][4]23 Although previous studies have shown that cardiac arousals without visually detectable EEG changes have been detected after respiratory events, 18,21,23,28 these respiratory events were found to be rarely associated with MAS contractions. This is consistent with the findings of the recent studies in which respiratory efforts and electromyography of the tongue muscles were assessed in relation to respiratory events.…”
Section: Discussionmentioning
confidence: 99%
“…29,32 However, arousal-dependent MAS contractions are not explained solely by the association between the degree of respiratory efforts in relation to respiratory events, since the motor responsiveness of MAS muscle to mAR and AW did not differ between arousals with and without preceding respiratory events. Since arousals during sleep are not always coupled with respiratory events in patients with OSAS, 18,23,28 the lack of difference in motor responsiveness between respiratory-related and spontaneous arousals, suggests that MAS contraction after a respiratory event is dependent on the arousal response rather than respiratory events per se.…”
Section: Discussionmentioning
confidence: 99%
“…In many studies they are identified based on the indications given by the ASDA [17]. Other authors prefer to analyse less evident EEG modifications [18][19][20][21]. In this study a similar definition was used to those given by MATHUR and DOUGLAS [19] and by REES et al [20], because it allows the visual identification of a high num-ber of sleep disturbances.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, in agreement with previous reports [6,[22][23][24], the current results suggest that the severity of nocturnal hypoxaemia, as opposed to sleep fragmentation, could be the primary determinant of impaired alertness, especially in severe OSAHS patients who exhibit numerous and deep sleep oxygen desaturation events. However, the role of arousals and awakenings should not be underestimated, since not all apnoeas and hypopnoeas are terminated by visible cortical arousals or awakenings [25,26] and, according to REES et al [27], this could be the case for ,30% of them. Fragmented sleep was assessed with only some parameters, whereas other measures of sleep fragmentation may better correlate with EEG spectral parameters, especially autonomic measures using cardiac activation during arousal [28].…”
Section: Discussionmentioning
confidence: 98%